The Development of English Teaching Material Base Local Wisdom at SMKN 1 Cinangka - Saputri, Sisca Wulansari; Rohiyatussakinah, Ina (Universitas Mathla'ul Anwar Banten, 2019)
This research aims to know the development result score of students using module which content local wisdom at SMKN 1 Cinangka. Teaching material in this research is module. This research method that uses is R&D method. This research uses 10 students with small group trial and 30 students with limited field trial. The researcher used technique of collecting data, such as; observation, interview, questionnaire and test. The result indicated that: after getting learning by using local wisdom module, there is any increasing for the score. The average score for experiment class is 54 become 81.5, and for control class is 48.5 and 63.5. It means that learning using local wisdom module got increasing score for experimental and control class.